Kajian Potensi Usaha Budidaya Ikan Lele (Clarias batrachus) (Studi kasus: “BUMdes Tengguli” di Desa Tengguli Kecamatan Sajad) - Januardy, Uray; Saifullah, Saifullah; Hanif, Hanif (Nekton, 2023)
Every fishery activity has potential which is highly dependent on the type of business and fishery resources available at the location of the activity. One of them is the potential for cultivating businesses in great demand by the community. The purpose of this research is to examine the potential for catfish farming in tarpaulin ponds at the Tengguli BUMDes. This type of research is quantitative research with a quantitative descriptive study approach. The research method uses financial analysis combined with environmental analysis focusing on water quality. The results of the research based on the financial aspect show that the costs incurred amount to IDR 8,986,166 including fixed costs and variable costs. Meanwhile, the profit earned was IDR 3,013,834/production. The BEP value is 299.5 kg/period at a minimum price of IDR 22,465.41/kg. An RCR value of 1.33 > 1 means efficient and profitable, a marketing margin of IDR 4,000, and a farmer's share value of 99% > 40% means efficient. While from the environmental aspect, the value of pH 5, temperature 29°C, DO 15.4 mg/l, nitrate 0 mg/L, phosphate 1.0 mg/L, and ammonia 0 mg/l did not cross the PP No. 82 of 2001 (class II).